Screening of Antibacterial, Thrombolytic, Membrane Stabilizing, Anti-inflammatory and Antitumor Activity of Citrus assamensis Leaf Extracts (Journal of Scientific Research, 2018)
The methanol, ethanol and chlorofom leaf extracts of Satkara, Citrus assamensis (family: Rutaceae), were subjected to in vitro anti-bacterial, thrombolytic, membrane stabilizing and in vivo anti-inflammatory and antitumor activity tests. The chloroform extract of C. assamensis showed the most important spectrum of activity against Bacillus subtilis, Bacillus cereus, Sarcina lutea among 6 gram positive and against 11 gram negative bacteria at the concentration of 1000 μg/disc, while the range of zones of inhibition were within 7-16 mm. Among the tested three extracts CHCl3 extract showed potent thrombolytic activity and hypotonic solution induced haemolytic activity where the percentages of inhibition were found to be 35% and 55% respectively. All the extracts established significant (p